Cyclooctane Metathesis Catalyzed by Silica‐Supported Tungsten Pentamethyl [(SiO)W(Me)5]: Distribution of Macrocyclic Alkanes. Issue 46 (3rd October 2014) - Riache, Nassima; Callens, Emmanuel; Samantaray, Manoja K.; Kharbatia, Najeh M.; Atiqullah, Muhammad; Basset, Jean‐Marie
Abstract Metathesis of cyclic alkanes catalyzed by the new surface complex [(SiO)W(Me)5] affords a wide distribution of cyclic and macrocyclic alkanes. The major products with the formula CnH2n are the result of either a ring contraction or ring expansion of cyclooctane leading to lower unsubstituted cyclic alkanes (5≤n≤7) and to an unprecedented distribution of unsubstituted macrocyclic alkanes (12≤n≤40), respectively, identified by GC/MS and by NMR spectroscopies.